Economic development in Tunisia : the impact and course of government planning - Duwaji, Ghazi (New York : Praeger, 1967)
A general account is given of the economy of Tunisia and of current development plans. The chapter on agriculture contains sections on the causes of the generally low yields in the traditional farming sector, the organization of agriculture with emphasis on attempts to promote the co-operative movement, the production of the main crops and the extent of livestock breeding by the nomad and semi-nomad part of the population, and on the agricultural development plan.
Includes bibliographical references: p. 213-222.
lje 25/01/2018
Loans
Keywords: Agricultural development; Economic development; Tunisia--Economic development